Assessment of esophageal motility disorders by real-time MRI. Issue 132 (November 2020) - Biggemann, Lorenz; Uhlig, Johannes; Gliem, Nina; Al-Bourini, Omar; Wedi, Edris; Ellenrieder, Volker; Ghadimi, Michael; Uecker, Martin; Frahm, Jens; Lotz, Joachim; Hosseini, Ali Seif Amir; Streit, Ulrike
Highlights: Real-time MRI visualizes esophageal bolus transit at a high temporal resolution. Esophageal motility disorders and GERD can have similar symptoms. Real-time MRI may help to identify patients with esophageal motility disorders. Abstract: Purpose: To investigate imaging findings of esophageal motility disorders on dynamic real-time. Material and methods: 102 patients with GERD-like symptoms were included in this retrospective study between 2015−2018. Dynamic real-time MRI visualized the transit of a 10 mL pineapple juice bolus through the esophagus and EGJ with a temporal resolution of 40 ms. Dynamic and anatomic parameters were measured by consensus reading. Imaging findings were compared to HRM utilizing the Chicago classification of esophageal motility disorders, v3.0. Results: All 102 patients completed real-time MRI in a median examination time of 15 min. On HRM, 14 patients presented with disorders with EGJ outlet obstruction (EGJOO) (13.7 %), 7 patients with major disorders of peristalsis (6.9 %), and 32 patients with minor disorders of peristalsis (31.4 %). HRM was normal in 49 patients (48.0 %). Incomplete bolus clearance was significantly more frequent in patients with esophageal motility disorders on HRM than in patients with normal HRM (p = 0.0002). In patients with motility disorders with EGJOO and major disorders of peristalsis, the esophageal diameter tended to be wider (23.6 ± 8.0 vs. 21.2 ± 3.5 mm, p = 0.089) and the sphincter length longer (19.7 ± 7.3 vs. 16.7 ± 3.0 mm, p = 0.091) compared to patients with normal HRM. 3/7 patients with achalasia type II were correctly identified by real-time MRI and one further achalasia type II patient was diagnosed with a motility disorder on MRI films. The other 3/7 patients presented no specific imaging features. Conclusion: Real-time MRI is an auxiliary diagnostic tool for the assessment of swallowing events. Imaging parameters may assist in the detection of esophageal motility disorders.